2014
DOI: 10.1002/asia.201402726
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiphilic Selenide Catalyst Behaves Like a Hybrid Mimic of Protein Disulfide Isomerase and Glutathione Peroxidase 7

Abstract: Protein disulfide isomerase (PDI) and glutathione peroxidase 7 (GPx7) cooperatively promote the oxidative folding of disulfide (SS)-containing proteins in endoplasmic reticulum by recognizing the nascent proteins to convert them into the native folds by means of SS formation and SS isomerization and by catalyzing reoxidation of reduced PDI with H2O2, respectively. In this study, new amphiphilic selenides with a long-chain alkyl group were designed as hybrid mimics of PDI and GPx7 and were applied to the refold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Compounds 5 and 6 were synthesized by applying a similar protocol reported previously [ 33 ] ( Scheme 2 ). Boc-protected mesylates 12a and 12b were first prepared from diethyl aminomalonate hydrochloride ( 10 ) or l -glutamic acid ( 11 ), respectively, by following previous methods with slight modifications [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 5 and 6 were synthesized by applying a similar protocol reported previously [ 33 ] ( Scheme 2 ). Boc-protected mesylates 12a and 12b were first prepared from diethyl aminomalonate hydrochloride ( 10 ) or l -glutamic acid ( 11 ), respectively, by following previous methods with slight modifications [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thioredoxin‐like domains containing cysteine residues (CXXC motifs) at PDI active sites inspired the development of disulfide‐ and diselenide‐based compounds as catalysts for in vitro oxidative protein folding and/or refolding (reactions A and/or D) . We recently reported that long‐chain, alkyl‐group‐conjugated cyclic monoselenides can recognize a reduced protein and catalytically introduce SS bonds randomly in a protein in the presence of H 2 O 2 (reaction B) . Thus, these PDI mimics mediated one or more out of reactions A, B, and D. Much less attention, however, has been directed towards SS reduction (reaction C).…”
Section: Methodsmentioning
confidence: 99%
“…The recovered enzymatic activity of HEL in the solution was estimated by the activity assay for HEL as described previously. [20]…”
Section: Oxidative Folding Of R Helmentioning
confidence: 99%
“…After centrifugation of the sample solution (14,000 rpm, for 3 min), the recovered enzymatic activity of HEL was estimated by the activity assay for HEL as described previously. [20] Oxidative folding of HEL at a high protein concentration R HEL solution (200 μM) dissolved in 100 mM Tris-HCl buffer solution containing 1 mM EDTA and 4 M urea at pH 7.5 were prepared as described above. The R HEL solution (50 μL) was mixed with 2.67 mM GSH (75 μL) and 0 or 533 μM diselenide compound or GSSG (75 μL), which were prepared by the solution without urea, and the resulting mixture was incubated at 37.0°C.…”
Section: Hplc Analysis Of Folding Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation